A rare case of plunging ranula with local recurrence and wide spread to the infratemporal fossa treated successfully by an intraoral surgical treatment. Issue 3 (May 2017) - Karino, Masaaki; Kanno, Takahiro; Iwahashi, Teruaki; Ide, Taichi; Kaneko, Ichiro; Yoshino, Aya; Sekine, Joji
Abstract: A ranula is a salivary gland cyst that typically presents as a localized superficial swelling on the floor of the mouth. A plunging ranula may develop when extravasation of mucus extends through or around the mylohyoid muscle and deeper into the neck, and can present as a neck lump with or without swelling on the oral floor. Here, we report a case of repeated local recurrence of a plunging ranula that expanded into the infratemporal fossa and was successfully treated by an intraoral surgical treatment. An 11-year-old otherwise healthy Japanese girl presented with extravasation and swelling in the left submandibular region, decreased flow of saliva from the sublingual and submandibular glands, and a 3 × 2 cm fluctuant swelling on the oral floor. Magnetic resonance imaging showed a large plunging ranula expanding to the infratemporal fossa. Surgical fenestration of the cyst wall and extirpation of the sublingual gland was performed using an intraoral approach. A Penrose drain was placed in the oral floor after fenestration of the cyst wall. The lesion was found to have expanded from the submandibular space to the infratemporal fossa through the parapharyngeal space. Drainage was effective, and the postoperative course was uneventful and without recurrence after 1.5 years of follow-up.